High‐altitude gravity waves in the Martian thermosphere observed by MAVEN/NGIMS and modeled by a gravity wave scheme. Issue 21 (5th November 2015) - Yiğit, Erdal; England, Scott L.; Liu, Guiping; Medvedev, Alexander S.; Mahaffy, Paul R.; Kuroda, Takeshi; Jakosky, Bruce M.
Abstract: First high‐altitude observations of gravity wave (GW)‐induced CO2 density perturbations in the Martian thermosphere retrieved from NASA's Neutral Gas Ion Mass Spectrometer (NGIMS) instrument on board the Mars Atmosphere Volatile EvolutioN (MAVEN) satellite are presented and interpreted using the extended GW parameterization of Yiğit et al. (2008) and the Mars Climate Database as an input. Observed relative density perturbations between 180 and 220 km of 20–40% demonstrate appreciable local time, latitude, and altitude variations. Modeling for the spatiotemporal conditions of the MAVEN observations suggests that GWs can directly propagate from the lower atmosphere to the thermosphere, produce appreciable dynamical effects, and likely contribute to the observed fluctuations. Modeled effects are somewhat smaller than the observed, but their highly variable nature is in qualitative agreement with observations. Possible reasons for discrepancies between modeling and measurements are discussed. Key Points: Wave‐like perturbations in the CO2 number density are observed by MAVEN Observed gravity wave signatures are highly variable Yiğit et al. (2008) scheme demonstrates GW propagation into the thermosphere